Gut Microbiome Diversity and Composition Are Associated with Habitual Dairy Intakes: A Cross-Sectional Study in Men. Issue 11 (12th August 2021) - Aslam, Hajara; Collier, Fiona; Davis, Jessica A; Quinn, Thomas P; O'Hely, Martin; Pasco, Julie A; Jacka, Felice N; Loughman, Amy
ABSTRACT: Background: At a population level, the relation between dairy consumption and gut microbiome composition is poorly understood. Objectives: We sought to study the cross-sectional associations between individual dairy foods (i.e., milk, yogurt, and cheese), as well as total dairy intake, and the gut microbiome composition in a large, representative sample of men living in south-eastern Australia. Methods: Data on 474 men (mean ± SD: 64.5 ± 13.5 y old) from the Geelong Osteoporosis Study were used to assess the cross-sectional association between dairy consumption and gut microbiome. Information on dairy intake was self-reported. Men were categorized as consumers and nonconsumers of milk, yogurt, cheese, and high- and low-fat milk. Milk, yogurt, and cheese intakes were summed to calculate the total dairy consumed per day and categorized into either low (<2.5 servings/d) or high (≥2.5 servings/d) total dairy groups. Fecal samples were analyzed using bacterial 16S ribosomal RNA (rRNA) gene sequencing. After assessment of α and β diversity, differential abundance analysis was performed to identify bacterial taxa associated with each of milk, yogurt, and cheese consumption compared with nonconsumption, low compared with high total dairy, and low- compared with high-fat milk consumption. All analyses were adjusted for potential confounders. Results: α Diversity was not associated with consumption of any of the dairy groups. Differences in β diversity were observed between milk and yogurt consumption compared with nonconsumption. Taxa belonging to the genera Ruminococcaceae UCG-010 and Bifidobacterium showed negative and weak positive associations with milk consumption, respectively. A taxon from the genus Streptococcus was positively associated with yogurt consumption, whereas a taxon from the genus Eisenbergiella was negatively associated with cheese consumption. No specific taxa were associated with low- compared with high-fat milk nor low compared with high total dairy consumption. Conclusions: In men, community-level microbiome differences were observed between consumers and nonconsumers of milk and yogurt. Bacterial taxon-level associations were detected with milk, yogurt, and cheese consumption. Total dairy consumption was not associated with any microbiome measures, suggesting that individual dairy foods may have differential roles in shaping the gut microbiome in men.